(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article provides a brief overview of mammary gland structural and functional characteristics of a non-pregnant virgin mammal and occurring morphofunctional changes during the dynamics of pregnancy and lactation.